Vulnerability Profile: Myanmar - United Nations Conference on Trade; Development (United Nations, 2022)
Prepared in the context of the process of Myanmar’s graduation from LDC status, this publication document contains insights into the particular vulnerabilities or fragilities of the country and the implications of these disadvantages. The profile helps national authorities understand the critical relationship between the need for resilience-building action, and LDC status as a basis for eligibility for special support to this action. It is organized around four pillars: (i) a situation analysis; (ii) identification of key areas of vulnerability; (iii) evaluation of the consequences of identified vulnerabilities; and (iv) identification of structures and features of the economy that are critical for a sustainable graduation and for reducing existing vulnerabilities. Topics covered include the socio-economic impact of COVID-19, pervasive informality, inequalities and gender issues.